Exploring students’ reactions when working teaching materials designed on their own interests (2015)
The current article describes the findings of a qualitative, descriptive-case study which aimed to explore the reactions of a group of students, after using didactic materials designed according to their interests. The population consisted of a group of fourteen EFL learners who started fifth level in the extension area, at Instituto Internacional de Idiomas (IIDI) of UPTC. A diagnostic survey was applied at the beginning of the process, in order to verify the issue. The study was framed under action research principles aiming at articulating possible solutions to some observed classroom problems related to students’ attitude in front of the English learning. The instruments used to collect data were a diary, students’ artifacts, and a final survey. The findings evidence that it is relevant to take students’ interests into account when planning a course since they can become the motor to encourage and improve the teaching- learning process, however, this is not enough, students’ commitment plays the main role.